Nonregular nonlinear sector modelling - Piegat, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
Fuzzy models realize human-like modelling schemes. However, a human being can create in his mind relatively simple models of real systems with maximum two inputs. The reason is that human models are based on rectangular lattice partitions of the input spaces. Such a partition enables us to understand the modelled system, which is a great advantage of fuzzy modelling. Despite this, the rectangular lattice partition makes modelling of systems with large numbers of inputs and those realizing complicated inputs/output mappings impossible or very difficult.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka